Perancangan Interior Perpustakaan Anak di Surabaya - Wijaya, Novia Andriani; Tulistyantoro, Lintu (Intra, 2016)
Reading interest in Indonesia is still relatively low, espescially children. It is caused by several things, such as technology development, lack of parental guidance, as well as the lack of facilities to provide library materials for children. This children’s library design has a goal to increase reading interest in Indonesia by implementing early reading habits. The concept used in the design is contrast. This concept uses contrast shapes and colors. The merger between cirlce and rectangle shapes and contrasting colors such as red, blue, yellow, and green create a colorful library with interesting formations so that children are interested to read in the library.